Membangun Mentalitas Pengusaha : Kunci Sukses dalam Dunia Bisnis - Kezia Almanda Oni Eki; Nur Lestari; Yosia Belo (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Building a successful entrepreneur mentality is a crucial step that requires time, experience, and a continuous commitment to learning and development. This mentality includes the ability to adapt to changes, manage risks, and maintain focus on long-term goals. Successful entrepreneurs are not only capable of responding to market changes and dynamic business conditions, but they also possess a flexible attitude and resilience in facing failure. Failure, when faced with a positive mindset, can become a valuable lesson that matures an entrepreneur. In the business world, success is not solely determined by external factors such as capital or networks, but also by perseverance, endurance, and an evolving mindset. Every entrepreneur's journey is unique, but a strong and resilient mentality is a key element in achieving long-term goals. Therefore, entrepreneurs need to continuously sharpen their mental capabilities to remain focused, motivated, and able to withstand various business challenges.